Should We Use Clinical Tools to Identify Disease Progression? - Inojosa, Hernan; Proschmann, Undine; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Neurology, 2021)
The presence of disability progression in multiple sclerosis (MS) is an important hallmark for MS patients in the course of their disease. The transition from relapsing remitting (RRMS) to secondary progressive forms of the disease (SPMS) represents a significant change in their quality of life and perception of the disease. It could also be a therapeutic key of opportunities, where different approaches than in the initial phases of the disease can be adopted. The characterization of structural biomarkers (e.g. magnetic resonance imaging or neurofilament light chain) has been proposed to differentiate between both phenotypes. However, there is no definite threshold between them. Whether the risk of clinical progression can be predicted by structural markers at early disease phases is still a focus of clinical research. However, several theories and pathological evidence suggest that both disease phenotypes are part of a continuum with common pathophysiological mechanisms. In this case, the clinical evaluation of the patients would play the preponderant role above destruction biomarkers for the early identification of disability progression and SPMS. For this purpose, the use of clinical tools beyond the Expanded Disability Status Scale (EDSS) should be considered. Besides established functional tests as the Multiple Sclerosis Functional Composite (MSFC), patient’s neurological history or digital resources may help the neurologists in the decision-taking. In this article, we discuss arguments for the use of clinical markers in the detection of secondary progressive MS and the characterization of progressive disease activity.